Antibody-Negative Relapse of Goodpasture Syndrome with Pulmonary Hemorrhage - Charlene L. Rohm; Sara Acree; Aseem Shrivastava; Asif A. Saberi; Louis Lovett (Case Reports in Medicine)
Goodpasture syndrome is a rare autoimmune disease comprising antiglomerular basement membrane (anti-GBM) crescentic glomerulonephritis and pulmonary capillaritis with circulating anti-GBM antibodies. Rarely, antibody-negative cases have been described. We report a young, African American adult woman admitted with flank pain and hematuria with laboratory testing and kidney biopsy demonstrating anti-GBM crescentic glomerulonephritis with elevated anti-GBM antibody levels. She received treatment but remained dialysis-dependent. She was seronegative and clinically stable until she presented 8 months later with dyspnea and hemoptysis requiring mechanical ventilation. Bronchoscopy revealed diffuse alveolar hemorrhage. She was treated for relapse of Goodpasture syndrome. However, anti-GBM antibodies were undetectable. This case emphasizes prompt diagnosis and treatment of Goodpasture syndrome to preserve renal function. Additionally, clinical manifestations of Goodpasture syndrome and its degree of activity do not necessarily correlate with the actual antibody titer on relapse. Clinicians should have enhanced awareness of this atypical presentation of a rare disease.